Incidence of Arrhythmias in Patients with Dengue Hemorrhagic Fever Presenting in Tertiary Care Hospital - Rashid Iqbal, Khawar Shoaib, Saira Khalid (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To determine the incidence of arrhythmias in patients with Dengue Hemorrhagic fever presenting in Tertiary care Hospital. Study Design: Retrospective Observational Study. Settings: This study was done in Department of Medicine, Sir Ganga Ram hospital Lahore. Timings: From 1-10-2022 to 31-12-2022. Methods: This paper describes the number of arrhythmia cases in Dengue hemorrhagic fever patients. We separated Dengue hemorrhagic fever patients from dengue fever patients and then divide Dengue hemorrhagic fever patients in two groups: Critical phase group and Recovery phase group. We picked up and analyzed the critical phase group to see the incidence of arrhythmias. We did so by interpreting files and charts of the patients admitted to Medicine department of Sir Ganga Ram Hospital, Lahore. We confirmed dengue hemorrhagic fever by checking the capillary leak phase of the patients by looking at ultrasound of abdomen for any signs of leakage, chest X-ray PA view, hematocrit and capillary refill time of the patients and then we tabulated the data. Results: A total number of 64 patients were selected during dengue epidemics from October 2022 to December 2022. Among 64 patients, Dengue fever patients were 23 (35.9 %) and dengue Hemorrhagic fever patients were 41 (64.1 %). Dengue Hemorrhagic fever patients were with in capillary leak phase. In Dengue Hemorrhagic fever patients, 14 patients (34.14 %) were having tachycardia in critical phase and 5 patients (12 %) were having bradycardia in critical phase. The present study was done with the aim to determine the clinical profile of dengue patients and to study the cardiac manifestations in patients with Dengue fever. Arrhythmias had been reported in literature but these were reported in recovery phase of dengue hemorrhagic fever 7,15. In dengue epidemic patients seen in our set up, bradycardia was seen in critical phase of dengue hemorrhagic fever 3. Previously bradycardia was reported in recovery phase of dengue hemorrhagic fever 2,16. In critical phase of dengue hemorrhagic fever there is chance of hypotension as fluid shifts to third space due to capillary leak. So bradycardia need to monitor carefully in critical phase. Very care full attention to fluid balance and hemodynamic monitoring is required in critical phase of Dengue hemorrhagic fever. This research will be helpful for careful monitoring of arrhythmias in critical phase of dengue hemorrhagic fever patients and results in decrease morbidity in dengue hemorrhagic patients in our community. Conclusion: Dengue virus induced arrhythmias were under reported but it is an important complication in Dengue Hemorrhagic patients. Bradycardia is one of cardiac complication can be present in critical phase of Dengue Hemorrhagic fever patients. Strict monitoring of patients with bradycardia is required in critical phase of Dengue Hemorrhagic patients. Keywords: Dengue Hemorrhagic Fever, Arrhythmias, Critical Phase.